Сurrent problems of improving the legislation of the Republic of Kazakhstan on prevention and suppression of offenses in the context of family and domestic relations - Oleinik , V.I. (Bulletin of the Karaganda University “Law Series”, 2021)
In Kazakhstan considerable attention is paid to issues of prevention of domestic violence. The main goal is not the reduction of impact and the imposition of only punitive measures, but the establishment of the causes and conditions contributing to the commission of these offenses, and their prevention. The task of all public authorities and organizations, the entire civil society is to ensure the high-quality implementation of state policy in countering domestic violence. The methodological basis of the research is the dialectical method of cognition, theoretical provisions of criminal law sciences, use of knowledge of such sciences as psychology, criminology, administrative law, as well as the theoretical and practical experience of foreign countries in this area. The main goal and objectives are to study the causes of family and domestic crime and develop organizational and legal measures to prevent it. At the same time, proven methods and principles of research were applied using practical experience and criminal law science. The author of the article examines the concept of family and domestic relations from the point of view of criminology, reveals the causes and social roots of criminal behavior in this area. The novelty of the study is that it was conducted in the context of the adoption and implementation of new laws in the field of countering domestic violence. The concepts of family and domestic crime, their characteristic and distinctive features, the existing problems of countering domestic crime in practice have been determined; proposals have been developed to increase the effectiveness of proceeding against offenses in this area. The practical significance of the study is expressed in the fact that the conclusions and recommendations formulated in the article will allow the subjects of prevention to develop a uniform practice of applying the norms related to the prevention and activation of counteraction to crimes committed in the field of family and domestic relations.